Exploratory study on the use of Internet by teachers of Institute of Technical Education, Singapore. - Tan, Mia Huan. (2008)
The purpose of this study was to investigate how vocational teachers in ITE Bishan were using the Internet and how they perceived the role of the Internet in the classroom. Potential usage and barriers to the usage of the Internet were also studied.